Heme Oxygenase-1: A Metabolic Nike - Wegiel, Barbara (Mary Ann Liebert, Inc., 2014)
Significance: Heme degradation, which was described more than 30 years ago, is still very actively explored with many novel discoveries on its role in various disease models every year. Recent Advances: The heme oxygenases (HO) are metabolic enzymes that utilize NADPH and oxygen to break apart the heme moiety liberating biliverdin (BV), carbon monoxide (CO), and iron. Heme that is derived from hemoproteins can be toxic to the cells and if not removed immediately, it causes cell apoptosis and local inflammation. Elimination of heme from the milieu enables generation of three products that influences numerous metabolic changes in the cell. Critical Issues: CO has profound effects on mitochondria and cellular respiration and other hemoproteins to which it can bind and affect their function, while BV and bilirubin (BR), the substrate and product of BV, reductase, respectively, are potent antioxidants. Sequestration of iron into ferritin and its recycling in the tissues is a part of the homeodynamic processes that control oxidation-reduction in cellular metabolism. Further, heme is an important component of a number of metabolic enzymes, and, therefore, HO-1 plays an important role in the modulation of cellular bioenergetics. Future Directions: In this review, we describe the cross-talk between heme oxygenase-1 (HO-1) and its products with other metabolic pathways. HO-1, which we have labeled Nike, the goddess who personified victory, dictates triumph over pathophysiologic conditions, including diabetes, ischemia, and cancer. Antioxid. Redox Signal. 20, 1709–1722.